Federal reserve information during the great moderation - Antonello D'Agostino; Karl Whelan (University College Dublin, UCD School of Economics, 2007)
Using data from the period 1970-1991, Romer and Romer (2000) showed that Federal Reserve forecasts of inflation and output were superior to those provided by commercial forecasters. In this paper, we show that this superior forecasting performance deteriorated after 1991. Over the decade 1992-2001, the superior forecast accuracy of the Fed held only over a very short time horizon and was limited to its forecasts of inflation. In addition, the performance of both the Fed and the commercial forecasters in predicting inflation and output, relative to that of 'naive' benchmark models, dropped remarkably during this period.
hdl:10197/964
Keywords: 330; Wirtschaftsprognose; Inflationsrate; Gesamtwirtschaftliche Produktion; Zentralbank; Wirtschaftsforschungsinstitut; USA